Screening of siblings to patients with abdominal aortic aneurysms in Sweden. (4th May 2017) - Linné, Anneli; Forsberg, Johan; Leander, Karin; Hultgren, Rebecka
Abstract: Objective. The prevalence of Abdominal Aortic Aneurysm (AAA) is higher for First Degree Relatives to AAA-patients compared to the general population, regardless of sex. The prevalence of AAA is also higher in the North of Sweden compared to the Mid and South. A regional strong hereditary trait has been suggested as an explanation to this. The aim of this study was to investigate if siblings to AAA-patients in the North have a higher prevalence of AAA compared to siblings in the Mid-region. Design. Cohort study. Materials and Methods. All patients treated for AAA in a northern region (Norrbotten county, North) were screened for siblings. Consenting siblings, age 40–80, were examined ( n  = 379) with ultrasound. The results were compared to the previously published results of 150 ultrasound-screened siblings in the Mid-region (Stockholm county). Results. The male/female ratio in the sibling cohort was 48% vs 52%. The prevalence of AAA in siblings in the North was 37/379 (brothers 14%, sisters 6%). This was not different from the prevalence among the Mid-region siblings 16/150 (brothers 17%, sisters 6% ( p  = 0.75). The distribution of risk factors was similar in the two regions. Conclusion. The results reinforce the importance of a more systematic approach towards selective screening of all siblings to AAA patients. Ultrasound should be performed in all eligible siblings, since the distribution of AAA is similar over regions. A correlation between the familial distribution and the reported high prevalence of AAA in general population in the North could not be shown.